Numerical Study of Natural Ventilation in a Building Using CFD Analysis - S. LAGUMBAY, RANDY (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
A Computational Fluid Dynamics (CFD) analysis of the air temperature dis-tribution, airflow pattern and particle tracks in a naturally ventined building is conducted. The effect of changing the boundary condition to the air temperature fell and air movement is studied. The commercial software like CFX 5.4. I is used in the simulation and analysis of the physical model problem. Results show that changing the boundary condition will affect the air temperature distribution and air movement inside a building. The accuracy of the solution will depend on the ercuracy of the wall boundary condition value